Recurrent pneumonia-H type Tracheoesophageal fistula, diagnostic dilemma. - Adhikari, S; Malla, K; Poudyal, P (Journal of Nepal Paediatric Society, 2014)
Tracheoesophageal fistula (TEF) without associated esophageal atresia (EA) is a rare congenital anomaly. Most of the children are treated for episodes of pneumonia prior to definitive diagnosis. A 5 months infant presented with recurrent pneumonia and diagnosis of H type TEF was made with contrast esophagram. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8517 J Nepal Paediatr Soc 2014;34(1):71-73